Enhancing immunotherapy outcomes by targeted remodeling of the tumor microenvironment via combined cGAS-STING pathway strategies - Huang, Mingqing; Cha, Zhuocen; Liu, Rui; Lin, Mengping; Gafoor, Naif Abdul; Kong, Tong; Ge, Fei; Chen, Wenlin (Frontiers in Immunology, 2024)
Immune checkpoint inhibitors (ICIs) represent a groundbreaking advance in the treatment of malignancies such as melanoma and non-small cell lung cancer, showcasing substantial therapeutic benefits. Nonetheless, the efficacy of ICIs is limited to a small subset of patients, primarily benefiting those with "hot" tumors characterized by significant immune infiltration. The challenge of converting "cold" tumors, which exhibit minimal immune activity, into "hot" tumors to enhance their responsiveness to ICIs is a critical and complex area of current research. Central to this endeavor is the activation of the cGAS-STING pathway, a pivotal nexus between innate and adaptive immunity. This pathway's activation promotes the production of type I interferon (IFN) and the recruitment of CD8+ T cells, thereby transforming the tumor microenvironment (TME) from "cold" to "hot". This review comprehensively explores the cGAS-STING pathway's role in reconditioning the TME, detailing the underlying mechanisms of innate and adaptive immunity and highlighting the contributions of various immune cells to tumor immunity. Furthermore, we delve into the latest clinical research on STING agonists and their potential in combination therapies, targeting this pathway. The discussion concludes with an examination of the challenges facing the advancement of promising STING agonists in clinical trials and the pressing issues within the cGAS-STING signaling pathway research.